Is Competition the Default Configuration of Cross‐Sensory Interactions? - Monti, Melissa; Molholm, Sophie; Foxe, John J.; Cuppini, Cristiano (The European journal of neuroscience, 2025)
ABSTRACT Several theories have been proposed about the default configuration of the brain's networks underlying unisensory and multisensory processing abilities and the development of multisensory integration during childhood. Recent empirical findings from animal models and behavioral data collected from typically developing (TD) children and children with autism spectrum disorder (ASD), however, are consistent with the idea that in the immature brain, prior to systematic cross‐sensory exposures typically encountered in everyday life, the individual sensory systems interact in a competitive manner. Which neural architecture and mechanisms best describe the brain's naïve configuration are still unknown. To fill this gap, this study investigates how sensory modalities interact in the young brain by comparing the predictions of two alternative biologically plausible neuro‐computational models to empirical data. The neural substrates responsible for the altered development of multisensory integrative processes observed in ASD children are also investigated. Linking the framework suggested by empirical data to a plausible neural implementation, our results challenge the classical notion of cross‐sensory brain organization at birth, whereby the various sensory pathways do not initially interact. Instead, we suggest that direct inhibitory interactions between sensory modalities are taking place in the immature brain, and we suggest that these inhibitory interactions play a crucial role in the altered multisensory perceptual abilities of children with autism. Neurocomputational modelling suggests that early cross‐sensory interactions are inherently competitive. Replicating ASD behavioral data requires stronger cross‐sensory competition, consistent with the hypothesis of delayed maturation.